2022
DOI: 10.3390/nu14071410
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ketone Bodies on Circadian Processes Regarding Appetite, Sleep and Hormone Release: A Systematic Review of the Literature

Abstract: Chrononutrition is an emerging branch of chronobiology focusing on the profound interactions between biological rhythms and metabolism. This framework suggests that, just like all biological processes, even nutrition follows a circadian pattern. Recent findings elucidated the metabolic roles of circadian clocks in the regulation of both hormone release and the daily feeding–fasting cycle. Apart from serving as energy fuel, ketone bodies play pivotal roles as signaling mediators and drivers of gene transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 123 publications
(135 reference statements)
0
19
0
Order By: Relevance
“…In the few available studies, there is insufficient evidence for the positive effects of alternate day fasting on glucose homeostasis, metabolic regulation and cardiovascular health [ 16 , 46 ]. It is known that TSH is a hormone that shows a circadian rhythm [ 47 ]. Independent of PCOS, TSH has been shown to increase after ketogenic diet [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the few available studies, there is insufficient evidence for the positive effects of alternate day fasting on glucose homeostasis, metabolic regulation and cardiovascular health [ 16 , 46 ]. It is known that TSH is a hormone that shows a circadian rhythm [ 47 ]. Independent of PCOS, TSH has been shown to increase after ketogenic diet [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that TSH is a hormone that shows a circadian rhythm [ 47 ]. Independent of PCOS, TSH has been shown to increase after ketogenic diet [ 47 ]. In our study, it was shown that TSH increased with TRF diet in patients with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…For cachectic patients, this presents a daily nutritional stress that can drive progressive lean wasting. The canonical metabolic response to fasting is to utilize stored lipids, and, as a result, humans experience the highest levels of blood ketones during their sleep hours (Masi et al, 2022; McGarry and Foster, 1971). In the absence of lipid oxidation, the liver must utilize other substrates for gluconeogenic and ketogenic metabolism, such as glycogen and amino acids mobilized from the muscle (Felig, 1973; Rémésy and Demigné, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, they have a big impact on signalling, affecting things like protein posttranslational modification. They also govern oxidative stress and inflammation, which emphasizes their significance for cellular function and overall metabolic management [21].…”
Section: Effects Of Beta-hydroxybutyrate In Traumatic Brain Injurymentioning
confidence: 99%